MEMBANGUN MUTU PEMBELAJARAN BAHASA ARAB - Mohammad Makinuddin (MIYAH : Jurnal Studi Islam, 2023)
Abstract: This research aims to identify the factors influencing the quality of Arabic language education and formulate effective recommendations and strategies to build a sustainable culture of quality in Arabic language learning. The research method used is a literature study, which involves searching for and analyzing relevant literature on Arabic language learning, factors influencing the quality of Arabic language education, and effective strategies and approaches in building a sustainable culture of quality. The recommended strategies for building a culture of quality in Arabic language learning include the following steps: firstly, formulating high standards of attitudes and behaviors for all members of the school; secondly, implementing a standard of excellent service within the school; thirdly, organizing competitions in Arabic language learning; fourthly, implementing a system of recognition and mentoring; and fifthly, enhancing the abilities of school members in Arabic language learning. Furthermore, efforts such as formulating learning standards, using varied approaches and methods, utilizing technology, project-based learning, authentic assessment, and teacher training can effectively enhance the quality of Arabic language education. The main objective is to actively engage and ensure the success of students in learning the Arabic language. By considering these factors and implementing the recommended strategies, it is hoped that Arabic language learning can achieve high and sustainable quality, as well as provide positive benefits to all stakeholders involved in the Arabic language learning process. Keywords: Quality Culture, Arabic Language Learning